DEVELOPING A MODEL TO PRODUCE ELITE AMATEUR GOLFERS IN MALAYSIA: A CONCEPT PAPER - Mohd Rom Muslim; Md Zawawi Abu Bakar; Zainudin Omar (Journal of Islamic, Social, Economics and Development, 2021)
The Sport Policy Factors Leading to International Sporting Success also known asSPLISS model identified nine pillars or policy areas that influence elite sporting success. Theresearch was initially an international comparative study on the relationship between elitesports policy and international sporting success of nations and to benchmark against othercompetitors. In Malaysia, there are gaps on the relationship between the elite sports policy ingolf specific and its international sporting success. This research intends to use the model todetermine the relationship of effective sports policy in golf and the generation of elite amateurgolfers who can win at the international level. The nine pillars that determine the effectivenessand efficiency of elite policies are financial support, structure and governance in elite sport,sports participation, talent identification and development, (post) athletic career support,training facilities, coach education and support, international competition and scientificresearch and innovation. This paper also aims to evaluate how these throughputs are appliedin order to maximize the possibility of Malaysian amateur golfers become successful ininternational competitions and improve their world amateur rankings. This concept paperintends to be an introduction to a new model that will be beneficial to the national governingbody (NGB) responsible for the policy and development of elite amateur golfers in this country.